TINDAK TUTUR ILOKUSI DALAM ACARA PODCAST DEDDY CORBUZIER PADA EPISODE SYEKH ALI JABER, SAYA PASRAH - Sari, Nilam; Sunarsih, Eti; Fitri, Fitri (Lafadz Jaya Publisher, 2024)
This research was conducted to describe illocutionary speech acts in Deddy Corbuzier's Podcast on Syekh Ali Jaber's Episode, Saya Pasrah, and to describe the implementation of the results of research on learning implementation plans in schools. This study uses descriptive methods and qualitative research forms. Data collection techniques used are observing techniques and note taking techniques. The results of the research conducted show that there are 5 types of illocutionary in the Deddy Corbuzier podcast on the episode of Syekh Ali Jaber, I surrender, namely 20 data in assertive form illocutionary speech acts, 9 data in directive illocutionary speech acts, illocutionary speech acts in expressive forms there are 7 data, there are 2 data for commissive illocutionary speech acts, 3 data for declarative illocutionary speech acts, so in total the data found is 41 data from 59 minutes 21 seconds on Deddy Corbuzier's Podcast on the Episode